'Good when they want to be': migrant workers in the supermarket supply chain. (3rd January 2012) - Thompson, Paul; Newsome, Kirsty; Commander, Joanna
<x xml:space="preserve">Abstract</x> Despite the increased attention paid to the role and effects of migrant labour in the contemporary economy, there has been insufficient attention to the role of employers and the employment relationship. Recent studies have highlighted distinctive labour power characteristics of new labour migrants from Central and Eastern Europe that make them 'good workers' in the eyes of employers. Drawing on multiple case studies across the supermarket supply chain, this article explores what kind of human resource migrant labour is perceived to be, particularly by employers, and what happens in practice as the dynamic tensions of the employment relationship unfolds in particular sector contexts. It argues that utilisation is conditioned more by the requirements of temporal flexibility – framed by the dynamics of employment within the supply chain – than any essential features of migrant labour power.